Ten-year Development of General Practice in China：Opportunities and Challenges - YANG Hui, HAN Jianjun, XU Yanli, GAO Xiaohuan, WANG Yang, YANG Yunli, CAO Xinyang (Zhongguo quanke yixue, 2022)
ObjectiveTo review the strengths and limitations of the development of general practice in China during the last decade (2010—2020) and to assess the opportunities and challenges for its future development.MethodsData were collected from statistic reports, journal articles and official policies and guidelines regarding general practice development in China from 2010—2020. Donabedian model was applied to examine and assess the quality of essential general practice services in China. SWOT analysis was used to identify internal and external determinants of general practice development in China.Results(1) Structural quality of general practice: the ten-year policies about general practice development were a continuation of the past relevant policies in essence but with developments, with highlights on continuous construction of general practice workforce and discipline, tiered diagnosis and treatment and regional medical consortium, but relevant fiscal and management policies still need improvements. The number of general medical workers has increased rapidly, while the lion's share of them are still allocated at tertiary hospitals. Full-time equivalent is suggested to be used to predict the staffing and assess the performance of these workers. The number of community health centres showed a steady increase, but its growth rate was still slower than that of hospital facilities. Relevant health economics data need to be further supplemented. (2) Process quality of general practice: in 2020, there were 2.045 billion visits in community health centers (stations) and township health centers, that is, 1.5 visits per person per year on average. There was a significant development when found only 1 visit per person per year for primary care in 2010. However, the frequency of visits for primary care was still lower than that of visiting hospital-based outpatients (an average of 2.7 visits per person per year) . The COVID-19 pandemic had a significant impact on community health services/general medical services, and the number of outpatient visits dropped by about 20%. The number of general practice research articles reached a peak in 2018, mainly focusing on bi-directional referrals, tiered diagnosis and treatment, general practitioners (GPs) /family doctors, general medicine, community health services, chronic disease management (especially hypertension and diabetes) , and analysis of factors associated with aspects involved in general medical services. General practice research is expected to provide more support for developing innovative and critical thoughts, more practice-based evidence for clinical services, and more assistance for service quality and patient outcomes improvement as the discipline advances. (3) Results of implementing general medical services: there is no sufficient evidence on the influence of general medical services on people's health. The experiences and views of people including healthy individuals and patients indicated that those receiving general medical services or contracted family doctor services perceived positive experience and expressed high satisfaction, but perceptions and views of general population in the community toward general medical services need to be explored. GPs' own experience and opinions on general practice were quite different. Gender, age, professional title, urban and rural areas, and geographical location may be associated with their experience and job satisfaction. There may be instability in the general practice workforce, mainly due to personal income, workload and time pressure. (4) The major strengths of developing general practice in China are as follows: strong policy-based promotion and government leadership; rapidly constructing and developing GPs teams owing to the excellent resource allocating ability shown by the centralized system from central to all local governments; significantly enhanced general practice education and training systems; increased core professionals as general practice educators and trainers; special development of general practice characterized by the integration of medical sciences and Chinese traditional humanistic theories. (5) The development of general practice in China has been facing limitations similar to those in other countries. Besides that, its special limitations include late development of the discipline, unsatisfactory quality of workforce, high work pressure and high prevalence of burnout in the workforce, as well as impact of generation gap on education and practice among GPs. In addition, the relation between specialists and GPs is on transition of from undifferentiated attachment to self-recognised uniquity, and further seeking transdisciplinary. The teaching competences of GPs teachers, especially those teaching community and clinical care, are inadequate. GPs team building and management need to advance from the formation to the storming and performing phases. (6) Opportunities for further development of general practice in China include strategies for achieving the goals of Healthy China, and an all-round well-off society, the important role of primary health care in sustainable development and universal health coverage reaffirmed by the Declaration of Astana, as well as significantly improved health literacy of people. (7) Challenges for the development of general practice in China include population ageing, and aging-related changes in burden of disease and socio-economic status, the aging and dynamic changes of GPs human resources, the variation of urban and rural areas and regional differences, and the inverted pyramid structure of allocation of medical and health resources (namely, the largest part is allocated to tertiary care while the smallest to primary care) . Relevant recommendations to address these challenges comprise strengthening the advocacy of the development of general practice services, establishing a wide-ranging community collaborative network, and developing general practice professional organizations.ConclusionThe development of general practice in China is advancing, which is manifested as rapidly increased number of general medical workers, strong government promotion, quickly improved accessibility of essential medical services, and notably increased utilization rate of primary care services. However, the development is facing challenges, such as high discipline and social expectations regarding general practice, instability in the workforce due to high work pressure of the knowledge- and labor-intensive job, GPs' insufficient recognition of their self-identity, and unclear status of financial funding for general practice development. Given that there are unprecedented favorable conditions for general practice development, medical industries and general medical workers are suggested to make efforts to turn challenges into opportunities to develop general medical services, thereby universal health outcomes will be improved.